2008
DOI: 10.1007/s00128-008-9511-9
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Organophosphorus Pesticide Residues in Vegetables of Agricultural Area in Venezuela

Abstract: The purpose of this study was to determine the residues of seven pesticides organophosphorus (methamidophos, diazinon, chlorpyriphos, parathion-methyl, dimethoate, malathion and tetrachlorvinphos), in some vegetables like: potato, lettuce, tomato, onion, red pepper and green onion cultivated in José María Vargas County in Táchira State, Venezuela. The research permitted to detect that 48.0% of the samples were contaminated with some of the pesticides studied. Methamidophos was founded in the vegetables in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 9 publications
0
10
0
1
Order By: Relevance
“…The presence of pesticide residues in vegetables has become a global phenomenon. Authors have reported the residues of OCs, OPs and SPs, along with fungicide and herbicides in fruit and vegetables from India (Dikshit et al 1990;Kumari et al 2002Kumari et al , 2003aKumari et al , b, 2006Shahi et al 2005;Bhanti and Taneja 2005) and abroad (Frank et al 1987;Wang et al 2008;Quintero et al 2008). Further, the persistence and half-life period of many pesticides were found to be less in tropical countries (Rup et al 1989).…”
Section: Resultsmentioning
confidence: 91%
“…The presence of pesticide residues in vegetables has become a global phenomenon. Authors have reported the residues of OCs, OPs and SPs, along with fungicide and herbicides in fruit and vegetables from India (Dikshit et al 1990;Kumari et al 2002Kumari et al , 2003aKumari et al , b, 2006Shahi et al 2005;Bhanti and Taneja 2005) and abroad (Frank et al 1987;Wang et al 2008;Quintero et al 2008). Further, the persistence and half-life period of many pesticides were found to be less in tropical countries (Rup et al 1989).…”
Section: Resultsmentioning
confidence: 91%
“…Apart from the potential danger they may pose to the soil organisms, there is also the possibility of translocation of these residues from the soil into cocoa fruits through the root system, and into other crops like vegetables that are commonly intercropped within cocoa farms, thereby constituting serious health risks (Townsend & Specht, 1975;Quintero et al, 2008). Contamination of surrounding water bodies by pesticides residues through runoff from contaminated farm soils is also likely as widely reported (Castilho, Fenzl, Guillen & Nascimento, 2000;Konstantinou, Hela, & Albanis, 2006;Pazou et al, 2006;Sarkar et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…In all of these countries, the organophosphate methamidophos is frequently used and is within the list of adverse residues. This pesticide is also detected in a review (Quintero et al 2008) done on the occurrence of organophosphate pesticides in six different vegetables from Venezuela. Although not in the list of pesticides used by farmers in the present study, methamidophos was also detected in celery originated from Suriname in a concentration higher than the MRL.…”
Section: Discussionmentioning
confidence: 77%